Seasonal variation of common skin diseases in pediatric age group a retrospective study conducted in a medical college of Nepal - Shrestha, S; Jha, AK; Thapa, DP; Bhattarai, CK (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Seasonal variation in disease frequency has been observed for centuries. The direct effects of climate on the skin play a small but significant role in determining the geographical and seasonal variation of many skin disorders also in pediatric age group. In our country Nepal where there is a wide range of climates and where pediatric population of 0 to 14 years constitutes 34.19% of the total population there is a need for studying the seasonal variation of pediatric dermatoses separately. MATERIAL AND METHODS: A retrospective study was conducted in the outpatient department of dermatology of Nepal Medical College and Teaching Hospital for a period of 1 year. The total patients were divided according to 4 seasons spring, summer, autumn and winter and analyzed with Chi square test. RESULTS: Out of total 2032 patients 52% was male and 48% was female. Majority of the visits was in the winter season, followed by summer, spring and autumn. The five most common dermatological problems in the pediatric age group were impetigo, lichen urticatus, scabies, seborrheic eczema and milaria. lichen urticatus, seborrheic eczema and milaria showed statistically very significant seasonal variation but impetigo and scabies did not. The age wise variation of these common dermatoses was also statistically highly significant. CONCLUSION: Many common dermatoses in the pediatric age group show seasonal variation and age wise variation. DOI: http://dx.doi.org/10.3126/jucms.v2i1.10483 Journal of Universal College of Medical Sciences (2014) Vol.2(1): 7-11